Leishmanicidal Effects of Allium giganteum Saponin-Rich Fraction on Leishmania major - Abbasali Eskandarain; Masoud Sadeghi Dinani; Omid Changiz; Simindokht Soleimanifard* (Iranian Society of Pharmacognosy, 2020)
Background and objectives: Leishmaniasis is caused by the genus of Leishmania and is one of the important health problems worldwide. Serious side effects, the lack of effective vaccines and the emergence of drug resistance are the major weak points of leishmaniasis treatment. The purpose of this study was to evaluate leishmanicidal effects of Allium giganteum saponin rich fraction, natural compounds with history of antimicrobial properties, on promastigotes and axenic amastigotes of L. major and macrophages cell line J774. Methods: The chloroform-methanol (9:1) extract of the flowers was fractionated by MPLC using an RP-18 column. The saponin-rich fraction was detected by TLC and H-NMR analyses and evaluated for leishmanicidal activity on L. major and macrophages cell line J774 using MTT assay at 24, 48 and 72 h of incubation. Results: At concentrations of 75, 100 and 150 μg/mL, over the time of 24 to 72 h, a significant decrease in the live parasite's rate was observed (p <0.05). At 200 μg/mL concentration, all parasites were killed and maximum leishmanicidal effect was observed. The IC50s for promastigotes and axenic amastigotes were 90.01 ± 13.42 μg/mL and 29.76±17.91 μg/mL, respectively; the value for the J774 macrophage cell line was 33.17±4 μg/mL. Conclusion: The results of this study showed the significant leishmanicidal effect of saponin rich fraction from Allium giganteum on promastigote and axenic amastigote of L. major and macrophage cell line in vitro. Complementary in vivo studies for evaluating the effects of the fraction on leishmaniasis in BALB/c mice is recommended.